2016
DOI: 10.1093/gbe/evw096
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Two Closely RelatedWolbachiawith Different Reproductive Effects on Hosts

Abstract: Wolbachia pipientis are obligate intracellular bacteria commonly found in many arthropods. They can induce various reproductive alterations in hosts, including cytoplasmic incompatibility, male-killing, feminization, and parthenogenetic development, and can provide host protection against some viruses and other pathogens. Wolbachia differ from many other primary endosymbionts in arthropods because they undergo frequent horizontal transmission between hosts and are well known for an abundance of mobile elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 103 publications
2
35
0
Order By: Relevance
“…The genomes of many arthropod heritable endosymbionts have now been assembled, however very few of those sequenced are associated with Lepidoptera hosts. A comparative genomics approach can be used to elucidate endosymbiont evolution and function in its host including identifying candidate genes involved in reproductive manipulations such as CI (as in Drosophila (Sutton et al, 2014;LePage et al, 2017)), and parthenogenesis induction (in parasitoid wasps (Newton et al, 2016;Lindsey et al, 2016)). A recent comparison of 16 Wolbachia genomes identified a core Wolbachia genome of 496 sets of orthologous genes, 14 of which were unique to Wolbachia among the Rickettsiales bacteria, of which it is a member (Lindsey et al, 2016).…”
Section: Comparative Endosymbiont Genomicsmentioning
confidence: 99%
“…The genomes of many arthropod heritable endosymbionts have now been assembled, however very few of those sequenced are associated with Lepidoptera hosts. A comparative genomics approach can be used to elucidate endosymbiont evolution and function in its host including identifying candidate genes involved in reproductive manipulations such as CI (as in Drosophila (Sutton et al, 2014;LePage et al, 2017)), and parthenogenesis induction (in parasitoid wasps (Newton et al, 2016;Lindsey et al, 2016)). A recent comparison of 16 Wolbachia genomes identified a core Wolbachia genome of 496 sets of orthologous genes, 14 of which were unique to Wolbachia among the Rickettsiales bacteria, of which it is a member (Lindsey et al, 2016).…”
Section: Comparative Endosymbiont Genomicsmentioning
confidence: 99%
“…The mechanism by which Wolbachia induces CI has attracted considerable attention including multiple genomic comparisons and many elegant cytogenetic studies (Tram and Sullivan, 2002;Serbus et al, 2008;Newton et al, 2016). Recent studies have suggested that two adjacent Wolbachia genes (cidA/cifA and cidB/cifB) are involved in Wolbachia-mediated CI (Beckmann et al, 2017;LePage et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wolbachia is necessary for nematode growth and development, as the adult worms were retarded, ovaries degenerated, and embryos could not form when Wolbachia was remove from nematodes by antibiotics [6]. In insect hosts, Wolbachia can increase the host's fertility [7][8][9][10][11], and enhance the insect host's resistance to many pathogens (such as RNA virus) [12][13][14]. Wolbachia can also provide vitamins to the host and give the host a clear growth advantage in the face of adversity [1,15].…”
Section: Introductionmentioning
confidence: 99%